Hubungan Pengetahuan Ibu, Pendapatan, dan Sarana Air Bersih Terhadap Kejadian Diare Pada Balita di Wilayah Kerja PUSKESMAS Dompu Kota Kabupaten Dompu - Safitri, Nastiti Aisyah Defita; Mardiah, Aena; Sherliyanah, Sherliyanah; Benvenuto, Ananta Fittonia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the relationship between maternal knowledge, family income, and access to clean water with the incidence of diarrhea in children under five in the working area of Dompu Kota Public Health Center, Dompu Regency. The research employed a cross-sectional design involving 222 mothers with children under five as respondents. Data were collected through guided interviews using questionnaires and analyzed using the chi-square test. The study results showed that (1) 68.9% of children under five experienced diarrhea. (2) The majority of mothers had low levels of knowledge (54.5%) and came from families with low income (54.1%). (3) Bivariate analysis indicated a significant relationship between maternal knowledge (p=0.013) and family income (p=0.048) with the incidence of diarrhea. (4) There is no significant relationship was found between access to clean water and the incidence of diarrhea (p=0.291). (5) Risk factors for diarrhea include low maternal knowledge regarding prevention and economic constraints that limit access to sanitation and healthcare. This study emphasizes the importance of improving health education for mothers and enhancing socioeconomic conditions and environmental sanitation to reduce the prevalence of diarrhea in children under five.